2017
DOI: 10.3389/fimmu.2017.00910
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Repertoire-Scale Immunoglobulin Properties in Vaccine-Induced B-Cell Responses

Abstract: Recent advances in the next-generation sequencing of B-cell receptors (BCRs) enable the characterization of humoral responses at a repertoire-wide scale and provide the capability for identifying unique features of immune repertoires in response to disease, vaccination, or infection. Immunosequencing now readily generates 103–105 sequences per sample; however, statistical analysis of these repertoires is challenging because of the high genetic diversity of BCRs and the elaborate clonal relationships among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Like JSD, these tests compare probability distributions and hence there is no limitation to number of sequences. A mouse study used SK and KMS tests to compare the V family usage within GC B cell repertoire of animals vaccinated with complex Ebola virus-like particle and unvaccinated controls ( 125 ). Enhanced use of IGHV8 was observed in the vaccinated group.…”
Section: Statistical Analysis Of B Cell Repertoiresmentioning
confidence: 99%
“…Like JSD, these tests compare probability distributions and hence there is no limitation to number of sequences. A mouse study used SK and KMS tests to compare the V family usage within GC B cell repertoire of animals vaccinated with complex Ebola virus-like particle and unvaccinated controls ( 125 ). Enhanced use of IGHV8 was observed in the vaccinated group.…”
Section: Statistical Analysis Of B Cell Repertoiresmentioning
confidence: 99%
“…The number of VH-gene residues that had undergone somatic mutation ranged up to 28% with a mean of 10.9% (supplementary Table 2 and Table 1 ), consistent with reports of the degree of somatic mutation in responses to infection. 34 , 35 By subdivision of antibodies by V-gene, J-gene, and CDRH3 or CDRL3 length, 91 heavy chain clusters and 63 light chain clusters are formed; these are arranged into 130 clonal families schematically represented by their heavy/light chain pairing, and antigen specificity (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies looking at responses to vaccination with complex antigens in humans have demonstrated that in some cases, clonal diversity can increase during maturation rather than decrease as a result of clonal competition. 34 , 35 , 45 To utilize this diversity, we recovered a number of related clones from high-throughput single-cell isolation and complementary repertoire sequencing. Initial identification of related clones will, by necessity, be centered on CDR3 homology.…”
Section: Discussionmentioning
confidence: 99%
“…A B-cell clone or clonotype is defined as a group of antibody sequences derived from a common progenitor B cell (Hershberg et al, 2015) that often bind to the same epitope. Clone size reflects on repertoire diversity, which is related to age (Davydov et al, 2018), response to vaccination or infection (Khavrutskii et al, 2017), allergy (Wu et al, 2014), cancer (Zhang et al, 2019), among several other conditions. B-cell clone identification is crucial, and different approaches attempt to do it.…”
Section: Introductionmentioning
confidence: 99%